Pengaruh Kualitas Produk Dan Brand Image Terhadap Loyalitas Konsumen Dengan Kepuasan Konsumen Sebagai Variabel Intervening (Studi Kasus pada Secangkir Kopi Kota Malang) - Abidin, Zaenal; Khalikussabir, Khalikussabir; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract In order to examine how brand image and product quality affect customer loyalty for a cup of coffee in Malang City, this study used consumer happiness as an intervening variable. The methodology used in this study is quantitative. Questionnaires given to Malang City coffee drinkers served as the major source of data for this study, while records, journals, earlier studies, and other sources provided secondary data. Because the population employed in this study is unknown, the purposive sampling method a strategy for selecting respondents based on criteria was used to transfer the sampling. This approach yielded a total of 85 samples using a Likert scale in a questionnaire. In hypothesis testing, the t test is employed. The findings of the study demonstrate that customer loyalty is influenced by brand image and product quality. Customer loyalty benefits from brand image and product quality to some extent. Customer happiness and loyalty are positively and significantly impacted by product quality. Customer pleasure, on the other hand, has a beneficial and notable influence on brand loyalty. Keywords: Product Quality, Brand Image, Consumer Loyality, Consumer Satisfaction